Strategi Eliminasi Praktik Korupsi dan Penyalahgunaan Wewenang Pemerinah Daerah Dalam Pelayanan Perizinan di Kabupaten Banyuwangi - Maulana, Ahmad Affan; Pratama, Angga (JURNAL ANTI KORUPSI, 2022)
ABSTRACT After Government Regulation Number 24 of 2018 concerning Electronically Integrated Business Licensing Services, it turns out that there are still two stages that actually have loopholes and the possibility of corrupt practices and authority (maladministration). This stage is the process of fulfilling commitments for the type of business and the process of implementing investment. One of Banyuwangi district's strategies in anticipating corruption and maladministration is an integrated service with a single window system (SWS). These services are expected to improve the quality of the community through services that are fast, cheap, easy, transparent, certain and affordable. This paper explains how the potential for corruption and authority can occur and how the implementation of SWS as a strategy to eliminate acts against the law. This study uses a qualitative descriptive method. Data collection techniques were carried out by interviews, literature studies and documentation. this will provide in the implementation of SWS, then provide a solution. Constraints in the implementation of SWS that come from directly. Evaluations are assessed in the area of ​​institutions and authorities. Then possible solutions are outlined to solve the problem of implementing SWS. KEYWORDS : Strategy, Corruption, Abuse, Lice